Coronary dilators and cardioplegia - Romagnoli, Alexander (1981)
The distribution in the myocardium of cardioplegic solution is demonstrated in dog hearts with the aid of indocyanine green. When papaverine or nitroglycerin are added to the solution, a much improved diffusion is observed. Papaverine appears to be a better coronary dilator. We deduce from this observation that myocardial protection during ischemic arrest for open-heart surgery is enhanced considerably when coronary dilation is assured.